COMPREHENSIVE TREATMENT OF IRON DEFICIENCY ANEMIA IN PREGNANT ON BACKGROUND PLACENTA DYSFUNCTION - Zaporozhan, V.M.; Ancheva, I.A. (World of Medicine and Biology, 2014)
The aim of this work was to evaluate the clinical efficacy of complex treatment of iron deficiency anemia in the background of placental dysfunction. The pathogenetic therapy of iron deficiency anemia in pregnancy should include preparations of ferrous iron, which is the tool of choice for the correction of iron deficiency and hemoglobin level. There was shown that the manifestations of placental dysfunction do not affect the severity of iron deficiency anemia and the effectiveness of adjuvant therapy. The most pronounced dynamics was observed over the content of ferritin, which allows us to consider this figure as the most promising for clinical monitoring.
Keywords: iron deficiency anemia; placental dysfunction; pregnancy diagnosis; treatment